345 Structural Cardiac Defects and Vascular Anomalies in Vein of Galen Malformation Patients: A Multi-Institutional Cohort With Genetic Sequencing. (April 2023) - Piwowarczyk, Paulina; Moyer, Quentin; Mekbib, Kedous Y.; Kappel, Ari D.; Zhao, Shujuan; Shohfi, John; Smith, Hannah; Orbach, Darren; See, Alfred P.; Smith, Edward R.; Kahle, Kristopher
Abstract : INTRODUCTION: Vein of Galen malformations (VOGM) are rare, potentially lethal brain arteriovenous malformations (AVM). The roles of EPHB4, RASA1, and ACVRL1 have been described in VOGM pathogenesis, and previous studies have reported the co-occurrence of VOGM with cardiac and vascular disorders. METHODS: We queried our cross-institutional cohort of 129 VOGM patients with detailed genotypic and phenotypic data. Genetic samples from a subset of 114 VOGM probands, including 90 trios, underwent whole exome sequencing. RESULTS: We found that 9.3% of our patients had structural cardiac defects, as compared to 0.8-1.2% in the general population. Our cohort's cardiac defects included 3.9% with patent ductus arteriosus, compared to 0.1% in the general population, and 1.6% with atrial septal defect, a congenital condition previously connected to VOGM. 22.5% of our patients had vascular abnormalities, including 16.3% with cutaneous vascular lesions and 4.7% with recurrent epistaxis. One patient presented with VOGM and moyamoya disease. Our whole exome sequencing found that patients with damaging RASA1 mutations presented with significantly more cutaneous vascular lesions relative to the rest of the VOGM cohort (60% vs 16%, p = 0.007) and patients with damaging ACVRL1 mutations had significantly higher rates of recurrent epistaxis (50% vs 5%, p = 0.002). CONCLUSIONS: RASA1 is associated with capillary malformation-arteriovenous malformation syndrome (CM-AVM), and ACVRL1 is associated with hereditary hemorrhagic telangiectasia (HHT); CM-AVM and HHT are neurovascular disorders in which the VOGM phenotype is frequently encountered. Our findings demonstrate the high incidence of cardiac defects and vascular abnormalities in VOGM patients and the value of clinical sequencing of VOGM patients with these co-occurring clinical features.